Perkembangan Terapi Massage terhadap Penyembuhan Penyakit Vertigo - Rustam Yuliyanto (Universitas Negeri Semarang, 2016)
The objectives of research are to find out the progress of massage therapist on healing vertigo disease and way handling massage therapist to help healing vertigo. This study belonged to a developmental research with cross-sectional method and a causal comparative research with type ex post facto. The study is done to scrutinize one kind of events that have occurred and than coherent backward to know the factors that could cause of the incident. The whole sample consisted of 11 people who have the vertigo disease and has given massage therapist in the past. Technique of analyzing data employed in this research was a descripstive the percentage. The result of data analysis shows that the progress of massage therapist on healing vertigo disease categorized good. This can be seen from scale on the development of massage therapist on healing vertigo disease overall which is 92%, it means the percentage it is in good category. The implications that the healing of diseases vertigo is variables affecting the results of healing massage therapist. In the effort to develop massage therapist must be considered. This condition caused due to the sensation movement or taste motion from a body or environment surrounding with other symptoms that arise, especially from autonomous tissue caused by a disorder balance of the body by various condition or disease. This condition would affect on the progress of massage therapist.